A suppressive oligodeoxynucleotide expressing TTAGGG motifs modulates cellular energetics through the mTOR signaling pathway. (21st October 2019) - Yazar, Volkan; Kilic, Gizem; Bulut, Ozlem; Canavar Yildirim, Tugce; Yagci, Fuat C; Aykut, Gamze; Klinman, Dennis M; Gursel, Mayda; Gursel, Ihsan
Abstract : The immunosuppressive ODN A151 profoundly affects mTOR signaling Abstract: Abstract Immune-mediated inflammation must be down-regulated to facilitate tissue remodeling during homeostatic restoration of an inflammatory response. Uncontrolled or over-exuberant immune activation can cause autoimmune diseases, as well as tissue destruction. A151, the archetypal example of a chemically synthesized suppressive oligodeoxynucleotide (ODN) based on repetitive telomere-derived TTAGGG sequences, was shown to successfully down-regulate a variety of immune responses. However, the degree, duration and breadth of A151-induced transcriptome alterations remain elusive. Here, we performed a comprehensive microarray analysis in combination with Ingenuity Pathway Analysis (IPA) using murine splenocytes to investigate the underlying mechanism of A151-dependent immune suppression. Our results revealed that A151 significantly down-regulates critical mammalian target of rapamycin (mTOR) activators ( Pi3kcd, Pdpk1 and Rheb ), elements downstream of mTOR signaling ( Rps6ka1, Myc, Stat3 and Slc2a1 ), an important component of the mTORC2 protein complex ( Rictor ) and Mtor itself. The effects of A151 on mTOR signaling were dose- and time-dependent. Moreover, flow cytometry and immunoblotting analyses demonstrated that A151 is able to reverse mTOR phosphorylation comparably to the well-known mTOR inhibitor rapamycin. Furthermore, Seahorse metabolic assays showed an A151 ODN-induced decrease in both oxygen consumption and glycolysis implying that a metabolically inert state in macrophages could be triggered by A151 treatment. Overall, our findings suggested novel insights into the mechanism by which the immune system is metabolically modulated by A151 ODN.